2019
DOI: 10.1016/j.bonr.2019.100203
|View full text |Cite
|
Sign up to set email alerts
|

PI3K activation increases SDF-1 production and number of osteoclast precursors, and enhances SDF-1-mediated osteoclast precursor migration

Abstract: Our previous studies showed that in a mouse model in which PI3K-AKT activation was increased (YF mice), osteoclast numbers and levels of SDF-1, a chemokine, were augmented. The purpose of this study was to delineate the role of PI3K activation in regulating SDF-1 production and examine whether SDF-1 can stimulate differentiation and/or migration of osteoclast precursors. Using flow cytometric analysis, we demonstrated that compared to wild type mice, bone marrow of YF mice had increased numbers of CXCL12 abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Consistently, our study showed that miR-19a-3p activated PI3K/ AKT signaling pathway through suppressing the expression of PTEN. The above findings were further supported by the study reported by Adapala NS et al, which suggested that the activation of PI3K/AKT signaling pathway leads to the increase in osteoclast formation and resorption in vitro (38).…”
Section: Discussionsupporting
confidence: 80%
“…Consistently, our study showed that miR-19a-3p activated PI3K/ AKT signaling pathway through suppressing the expression of PTEN. The above findings were further supported by the study reported by Adapala NS et al, which suggested that the activation of PI3K/AKT signaling pathway leads to the increase in osteoclast formation and resorption in vitro (38).…”
Section: Discussionsupporting
confidence: 80%
“…Stromal cell derived factor-1 (SDF-1), also known as CXCL12, is critical for cell migration (Yu et al, 2003 ; Kollet et al, 2006 ; Gronthos et al, 2007 ). PI3K activates the transcription of SDF-1, resulting in the migration of osteoclast precursors via C-X-C chemokine receptor type 4 (CXCR4) (Adapala et al, 2019 ). Sphingosine-1-phosphate, a lipid mediator enriched in blood and lymph, can induce and regulate the homing of osteoclast precursors to bone (Ishii et al, 2009 ; Kikuta et al, 2013 ).…”
Section: Cell Fusion and Multinucleation Of Osteoclastsmentioning
confidence: 99%
“…Inotropic glutamate receptors’ activation demonstrates regulation of the OCs phenotype in vitro and maintenance of bone mass [ 34 , 35 ]. The PI3K-AKT pathway, which we also found in the group treated with the venom, is related to the increase in the number of osteoclasts and cytokines, with greater precursors’ effectiveness [ 36 ]. We also identify the pyrimidine pathway; it is known that extracellular nucleotides can play a role in bone regulation, signaling, and cartilage metabolism.…”
Section: Resultsmentioning
confidence: 99%